2019
DOI: 10.1167/tvst.8.6.17
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Optical Coherence Tomography Angiography in Uveitic Eyes

Abstract: PurposeTo investigate the intravisit repeatability of optical coherence tomography angiography (OCTA) in a cohort of uveitis patients.MethodsOne hundred ten patients were imaged twice per eye, per visit, using the Zeiss Cirrus HD-OCT Model 5000 device. To calculate choriocapillaris flow void area (CC FV) 6 × 6-mm images were used, and 3 × 3-mm images were used to calculate vessel density (VD) and the foveal avascular zone area (FAZ) of the superficial capillary plexus (SCP) and deep capillary plexus (DCP). Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The first objective of this study was to carry out a detailed phenotypic analysis and describe its morphologic and vascular changes in the CAG-HtrA1 Tg mice. Using several in vivo imaging modalities, specifically OCT and OCTA, we accurately obtained non-invasive deep morphological images of the retinal and choroidal layers together with their flow signals, suggestive of the vasculature, through tuneable lasers [ 15 , 21 , 22 ]. On OCT, CAG-HtrA1 Tg mice showed three-dimensional morphological changes of the yellow-white retinal foci and large white lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The first objective of this study was to carry out a detailed phenotypic analysis and describe its morphologic and vascular changes in the CAG-HtrA1 Tg mice. Using several in vivo imaging modalities, specifically OCT and OCTA, we accurately obtained non-invasive deep morphological images of the retinal and choroidal layers together with their flow signals, suggestive of the vasculature, through tuneable lasers [ 15 , 21 , 22 ]. On OCT, CAG-HtrA1 Tg mice showed three-dimensional morphological changes of the yellow-white retinal foci and large white lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies have reported on quantitative analysis of the retinal microvasculature using OCTA and have observed high repeatability and reproducibility. [22][23][24][25][26] In contrast, relatively few studies have addressed CC repeatability. 26,27 When evaluating repeatability with two repeated scans at the same position, our results showed a high ICC of 0.950 for CC FD, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] On en-face representations, OCTA can depict areas of choriocapillaris ow de cits and has demonstrated repeatability in uveitis patients. 10 The choriocapillaris ow de cits may represent absent ow or areas of ow that are too slow to be detectable by the OCTA platform. [11][12][13] Further, OCTA has the advantages of being a non-invasive imaging modality with a relatively short acquisition time that could be well utilized in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%